Probing the morphology of dust particles in deep ice cores with light scattering - Llorenç Cremonesi (Società italiana fisica, 2021)
The size distribution and light extinction cross-section of airborne particles are among the climate proxies investigated in palaeoclimate research and required by radiative transfer models. The optical properties of the particles are acquired by a non-invasive, single-particle light scattering technique to characterise aeolian dust stored in deep polar ice core samples. The same method is applied to study alpine ice cores and firn cores. The particle-by-particle approach provides a comprehensive statistical analysis while overcoming the limitations imposed by low concentrations (similar to 10(1)-10(3) ng/g). From a geometrical standpoint, dust particles deviate significantly from homogeneous spheres, as expected by many studies on mineral dust sources and ice core analysis. Features such as shape and structure prove to have greater importance than the particle refractive index in determining their radiative properties. By comparing experimental data to computationally inexpensive simulations, the main morphological properties of the particles can be inferred, such as the ratio between the axes in prolate particles and the porosity in isometric aggregate particles.